Royal counselors and nobles in Hincmar of Reims’s political concept - N. A. Fedonnikov (Шаги, 2023)
This article is devoted to the role of royal counselors and nobles in Hincmar of Reims’s political concept. The study is based on political instructions of the prelate of Reims, such as “De regis persona et regio ministerio” and “De ordine palatii”, as well as the letters of the archbishop and his compilation of the Annals of St Bertin. Analysis of Hincmar’s texts shows that royal power was based on harmony between the king, the nobility, and the clergy. Drawing attention to contemporary events, the prelate of Reims criticizes both representatives of the nobility in the Kingdom of the West Franks, and the kings who indulge them. In Hincmar’s opinion, the only way for a king to rule virtuously and rightfully is to rely on the advice of just and wise counselors. The virtues of the royal inner circle are the same as the virtues of the king: justice, mercy, wisdom, piety, humility. The Reims prelate envisions a bishop as the ideal royal advisor. Moreover, since the priest is responsible to the Lord for the king’s deeds, he must strictly observe the fulﬁlment of king’s duties. In this regard, Hincmar constructs the ofﬁce of an apocrisiarius-archcapellan, an envoy from the Frankish episcopate, who would supervise all church affairs at court and guide the king’s ethics as well.